2023
DOI: 10.1530/eor-22-0039
|View full text |Cite
|
Sign up to set email alerts
|

The modern state of femoral, acetabular, and global offsets in total hip arthroplasty: a narrative review

Abstract: Offsets in the frontal plane are important for hip function. Research on total hip arthroplasty (THA) surgery agrees that increasing femoral offset up to 5 mm could improve functional outcome measures. The literature indicates that global offset is a key parameter that physicians should restore within 5 mm during surgery and avoid decreasing. Substantiated findings on acetabular offset are lacking despite its recognized importance, and the medialization approach must be assessed in light of its shortcomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In this case, the acetabular preparation consists of reaming down to the true floor, thus medializing the hip’s rotation center and decreasing acetabular offset. This medialization dwindles the body weight’s lever arm during monopodial stance, diminishing the resultant force on the femoral head if every anatomic formation is intact[ 9 ]. Current literature focuses on reducing the acetabular offset in relation to the femoral offset, extensive criticism of this guideline has been observed[ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the acetabular preparation consists of reaming down to the true floor, thus medializing the hip’s rotation center and decreasing acetabular offset. This medialization dwindles the body weight’s lever arm during monopodial stance, diminishing the resultant force on the femoral head if every anatomic formation is intact[ 9 ]. Current literature focuses on reducing the acetabular offset in relation to the femoral offset, extensive criticism of this guideline has been observed[ 10 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic surgeons should ream the medial cotyloid cavity to the floor until a suitable component size for implantation. This triggers medial and superior displacement of the hip’s rotational center to achieve a comparatively normal acetabular offset and rotation center[ 9 ]. Additionally, the exact preoperative planning reduces surgical time and number of complications[ 3 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 FO was defined as the distance from the center of the femoral head to the bisector of the long axis of the femur. 13 Acetabular offset was defined as the distance from the center of the femoral head to the true floor of acetabulum. 14 Worlicek et al revealed the relationship between global FO and restoration of leg length and trochanteric pain syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Global FO was defined as the sum of the acetabular offset and FO 12 . FO was defined as the distance from the center of the femoral head to the bisector of the long axis of the femur 13 . Acetabular offset was defined as the distance from the center of the femoral head to the true floor of acetabulum 14 .…”
Section: Introductionmentioning
confidence: 99%